DESIGN AND IMPLEMENTATION OF AN INDOOR AIR QUALITY MONITORING SYSTEM BASED ON RASPBERRY PI AND ARDUINO PLATFORMS - I. Rudavskyi; L. Kovaliv; Halyna Klym (Електроніка та інформаційні технології, 2024)
This paper presents the development of a comprehensive system of monitoring of air quality in closed premises, which is built on the basis of the microcomputer Raspberry Pi 4 and the Arduino hardware. The developed system allows not only to monitor the parameters of air, but also acts to influence its quality. This is achieved through the use of auxiliary devices that ensure efficient air purification, as well as ventilation of the room to maintain comfort. The system contains key hardware components: air cleaner, ventilation unit and sound alarm. Their work ensures the maintenance of air quality at the optimum level and promptly inform the user about any dangerous changes in the composition of the air. Control is carried out by collecting data from sensors that measure air quality parameters every five minutes with the possibility of adjusting the renewal frequency. The information collected is transmitted to the Raspberry Pi, where the data is analyzed and displayed through a specially designed interface, which allows the user to quickly monitor the current state of the room. The sound alarm reports critical changes in the quality of air, such as increasing CO2 or the content of harmful substances. The system software is designed using Python and Tkinter, as well as Arduino IDE. This combination allows you to effectively organize the work of all components and ensure continuous monitoring of air quality. The wireless connection between the sensors and the central part of the system is implemented by Wi-Fi modules, which facilitates the installation and use of the system in any room. Experimental studies were conducted in two stages. In the first stage, the system worked in the conditions of ordinary office activity, where the basic air indicators during the workflow were recorded. In the second stage, which included physical activity, an increase in CO2 levels was recorded, which indicates increased air pollution in the conditions of active activity. This emphasizes the importance of regular air monitoring to maintain comfortable conditions in the room, especially during exercise. The results of the experiments confirm the efficiency of the monitoring and quality control system. The system is able to respond promptly to changes in the surrounding sector, providing timely air purification and maintaining it at a safe level, which is important for the health and comfortable stay of people indoors.